Powder Metallurgy Fundamentals and Case Studies - Dobrzanski, Leszek A. (IntechOpen, 2017)
The book presents the fundamentals and the role of powder metallurgy in contemporary technologies and the state of the art of classical powder metallurgy technologies and a general description of new variants and special and hybrid technologies used in powder metallurgy. The next part includes over a dozen case studies provided in the following chapters, comprehensively describing authors' accomplishments of numerous teams from different countries across the world in advanced research areas relating to powder metallurgy and to special and hybrid technologies. The detailed information, largely deriving from own and original research and R&D works pursued by the authors, will be beneficial for the readers to develop their knowledge and harmonise specific information concerning these topics and will convince the manufacturers about the advantages of using the powder metallurgy technology in many branches of industry.